Answer:
2x - y - 3 = 0
Explanation:
Find slope-intercept form first: y = mx + b
Step 1: Pick out 2 points
In this case, I picked out (2, 1) and (0, -3) from the graph
Step 2: Using slope formula y2 - y1/x2 - x1 to find slope
-3 - 1/0 - 2
m = 2
Step 3: Place slope formula results into point-slope form
y = 2x + b
Step 4: Plug in a point to find b
-3 = 2(0) + b
b = -3
Step 5: Write slope-intercept form
y = 2x - 3
Step 6: Move all variables and constants to one side
0 = 2x - 3 - y
Step 7: Rearrange
2x - y - 3 = 0 is your answer